Identifikasi Fungsi Dan Aktivitas Pada Taman Janggan Sebagai Ruang Terbuka Publik Kota Denpasar - Sholichin, Abdul; Kohdrata, Naniek; Sukewijaya, I Made (Jurnal Arsitektur Lansekap, 2023)
Identification of Functions and Activities in Janggan Park as a Public Open Space in Denpasar City. Janggan Park is an urban public open space, located in Denpasar City, Janggan Park has two parts of the park, namely the western and eastern parts, Janggan Park is also a park for relaxing the people of Denpasar City and is predicated as a child-friendly playground. This research was carried out to find out the irregularities in the activities and functions of the park between the western and eastern parts of the park and with this research it can provide advice to the government regarding future management. The method used in this research is field observation, interviews, and questionnaires. From the results of the study, it was found that park visitors prefer to have activities in the eastern part than the western part, which is the difference in activity between the western and eastern parks, namely because of differences in park management, so that the treatment patterns for both hardscape and softscape are different, the eastern part of the park is managed by the city government. Denpasar, while the western part is managed by the provincial government of Bali. The difference in management is what makes the vision of the park differ that effect the park condition. Plants selection and maintenance are two aspects that cause differences in visitors preferences in using the park.